Tarybinė knyga ir periodinė spauda buržuazinėje Lietuvoje (1919–1940) - Bartašienė, Irena (Knygotyra, 1985)
The Soviet book and periodical press spread in the bourgeois Lithuania under hard social political and cultural conditions. Nevertheless Soviet publications were very popular among the participants of revolutionary movement, advanced intelligentsia, workers. The book-shops “Science” („Mokslas“), “Literature” („Literatūra“), Teachers’ book-shop (Mokytojų knygynas) and others played a significant role in the reading of Soviet books and periodical press. The Soviet publications were complete and issued to the readers in the libraries. The Kaunas University library, the V. Kudirka library and others acquired and served to the readers the Soviet publications. The Lithuanian Society for Study of the Culture of Soviet Nations (1924–1940) was also engaged in the propaganda of Soviet books. The Soviet publications played an important role in the Lithuanian life in 1919–1940, they helped to learn about the various aspects of the life in the Soviet Union, to acquire the basic knowledge of Marxist-Leninist theory, furthered friendship among nations.